Hubungan Karakteristik Pedagang Ayam Potong dengan Tingkat Pelayanan Penjualan Ayam Hasil Pemotongan Standar Higienis - Yunasaf, Unang; Sulistyati, Marina; Nurlina, Lilis; Alim, Syahirul; Mauludin, M. Ali; Fitrini, Anita (Universitas Galuh, 2025)
Chicken meat is rich in protein and moisture, making it susceptible to rapid spoilage when exposed to harmful microorganisms. Therefore, it is essential to maintain high standards of hygiene and service during sales and slaughter processes. This study aims to explore the relationship between the characteristics of broiler chicken traders—such as age, education, business experience, sales volume, and income—and the level of service provided in selling chickens that meet hygienic standards. The research was conducted in September 2024 at Ciroyom Market, located in the Andir District of Bandung City, West Java. Respondents were chosen randomly, resulting in a sample size of 31 individuals. The Spearman Rank correlation test was employed to assess the relationship between the two variables. Findings indicate that most broiler chicken traders fall within the early adulthood age range (15–40 years), possess a medium level of education (junior high to senior high school), have significant business experience (over 10 years), and report a medium sales volume (2,708.40 – 18,736.76 kg/month) along with a medium income (Rp. 4,887,869.25 – Rp. 28,528,259.78/month). The service level of the majority of traders is categorized as medium (64.52%). The characteristics that demonstrate a significant correlation with the service level for selling hygienically slaughtered chickens are education, sales volume, and income, while age and experience do not show a significant correlation.